Kontribusi Model Pembelajaran Berbasis Proyek terhadap Prestasi Belajar Siswa di SD Asisi Fodo - Bunga Santaria Sinambela; Paulinus Kanisius Ndoa; Sitepanus Zebua (Journal New Light, 2024)
Project-based learning is a learning model that requires students to complete a project within a certain period of time, keeping them active and innovative. The purpose of this study is to determine the role of project learning model in the performance of Ashish Fodh SDS students. The research method used is qualitative data using observation, interview and documents. It was found in this research that teachers had not fully implemented the project-based learning model at SDS Asisi Fodo. Its application is only limited to a few classes. This is because the teacher does not have direction from the leadership and the teacher's ability is limited in implementing the project-based learning method. Teachers prefer to teach using lecture and discussion methods in class. In fact, in the Merdeka Belajar curriculum, Since this model of teaching is student-centered, teachers are expected to apply it. Therefore, the researcher hopes that the findings of this study will help the teachers of SDS Ashish Fodh to implement the project-based learning method and contribute to student achievement.